Emergence, risk and enactment: Advancing a multifocal approach to the study of violence - Bowman, Brett (My University, 2021)
Violence, in its many forms, remains a defining and seemingly intractable feature of modern life globally. This lecture outlines emergence, risk and enactment as three scholarly focal points for understanding violence in South Africa and beyond. It addresses how and why violence was first identified for study and intervention by the social and health sciences, describes the promises and limits of the current focus on risk, and reviews recent approaches to studying violence in situ that is, as it unfolds rather than how it is reported for counting or meaning making. The lecture then provides several suggestions for strategically fusing these focal points to produce the enhanced picture of violence required to take violence scholarship and intervention programming forward.
Keywords: Violence; Emergence; Risk; Enactment; South Africa; Social sciences; Health sciences